Religion-State Relationship Models. The Survival of an Instrument of Study in the Post-Secular Era - Palomino Lozano, Rafael (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
In Law and Religion studies, the analysis and discussion of models of State-religion relationship (i.e. secular State, non-denominational, theocratic, official religion state, etc.) is a topic of needed reference. Even if the models remain pedagogically useful for approaching legal relations of an institutional nature, however they are insufficient to address the complexity of the religious phenomenon in the post-secular era. This article unfolds some expressions of that complexity that escape explanation by means of these models and concludes that it is necessary to relativize the value of these relationship models, considering other relevant legal variables on religion and beliefs.